El WhatsApp para potenciar el aprendizaje del idioma inglés en los estudiantes de la Unidad Educativa Federico Froebel, Babahoyo.2022 - Lynch Becilla, Augusto Renato (2024)
This research explores the benefits of using messaging applications such as WhatsApp to improve English language learning. The study was carried out on a total of 92 Higher Basic General Education Students from the Federico Froebel 2022 Educational Unit. The work was carried out for 6 weeks, and was sent through a "WhatsApp" group. as well as an assessment used to analyze the degree to which students develop language skills and the types and triggers that lead to language-related episodes in chats; The research analyzes the degree to which students acquire language proficiency. This study uses a mixed analysis with measurement on the time axis to measure the variations observed between each student and provides complementary information about their interaction. The results show that the activities have led to significant improvements in the students' English language learning.